Academic writing strategies in university students from three disciplinary areas: design and validation of an instrument - Sagredo-Ortiz, Sindy; Kloss, Steffanie (Frontiers in Education, 2025)
It is acknowledged that writing strategies are highly important not only for their usefulness in the process of text production but also for their value as a learning technique, as they involve the use of cognitive and metacognitive operations. Various international studies have validated scales to measure their use and have helped characterize expert and non-expert university writers. However, regarding specific strategies in Spanish as a mother tongue, further research is still needed in the context of higher education students. This study aimed to develop a standardized measurement instrument to identify university students' use of academic writing strategies according to disciplinary area. The sample consisted of 290 students from the Humanities and Social Sciences, Health Sciences, and Engineering from a regional university in Chile. A Likert-type scale was applied whose design was based on a thorough review of successful instruments from different parts of the world. The results indicate that the developed instrument is appropriate for higher education contexts and across different disciplinary areas.